2019
DOI: 10.1155/2019/4730507
|View full text |Cite
|
Sign up to set email alerts
|

The IL-1B Gene Polymorphisms rs16944 and rs1143627 Contribute to an Increased Risk of Coronary Artery Lesions in Southern Chinese Children with Kawasaki Disease

Abstract: Background. Kawasaki disease (KD) is a systemic form of self-limited vasculitis in children less than five years old, and the main complication is coronary artery injury. However, the etiology of KD remains unclear. The IL-1B polymorphisms rs16944 GG and rs1143627 AA and their diplotype GA/GA have been associated with significantly increased risk of intravenous immunoglobulin (IVIG) resistance in a Taiwanese population, but the relationship between rs16944 A/G and rs1143627 G/A and coronary artery lesions (CAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
1
21
0
1
Order By: Relevance
“…The cytokine profile of the acute phase of the mouse model also bears strong similarity to that of the human disease, with elevations of IL-1b, TNF-a, IL-6, MCP-1, and IL-10 in the serum, as well as clinical symptoms of dysregulated temperature (20,22). Human transcriptome, human genetic data and experimental murine models of KD all support a key role for IL-1b in the pathogenesis of KD, and also show the effectiveness of the LCWE model in terms of translational features to humans, such as histopathologic and even echocardiographic changes (10)(11)(12)(13)(14)(15)(16)(17)(23)(24)(25)(26).. Furthermore, the mouse model reliably predicts treatment efficacy, including of IVIG treatment (22).…”
Section: Introductionmentioning
confidence: 95%
“…The cytokine profile of the acute phase of the mouse model also bears strong similarity to that of the human disease, with elevations of IL-1b, TNF-a, IL-6, MCP-1, and IL-10 in the serum, as well as clinical symptoms of dysregulated temperature (20,22). Human transcriptome, human genetic data and experimental murine models of KD all support a key role for IL-1b in the pathogenesis of KD, and also show the effectiveness of the LCWE model in terms of translational features to humans, such as histopathologic and even echocardiographic changes (10)(11)(12)(13)(14)(15)(16)(17)(23)(24)(25)(26).. Furthermore, the mouse model reliably predicts treatment efficacy, including of IVIG treatment (22).…”
Section: Introductionmentioning
confidence: 95%
“…Previous study based on Chinese children with KD showed the association of 2 genetic polymorphisms rs16944 GG and rs1143627 AA within IL-1B gene with the risk of coronary artery lesions in children younger than 12 months, which may contribute to the pathogenesis of KD. 43 However, we found no papers on CAD and PAI-1 and FXIII polymorphisms in children. In conclusion, the results of conducted systematic review along with meta-analyses based on large group of pediatric patients and controls showed that both PAI-1 and FXIII polymorphisms are not risk factors for AIS in children.…”
Section: Discussionmentioning
confidence: 80%
“…There are also increased levels of IL-1, TNF-a, and IL-6, and these cytokines correlate with development of coronary artery disease and IVIG nonresponsiveness [15,22,23]. Gene association studies have implicated polymorphisms in IL-1, TNF-a, IL-6, HLA, and Toll-like receptors indicative of immune responses in KS [24][25][26][27][28]. Finally, treatment of patients with IVIG and aspirin reduces the immune activation associated with this syndrome [29,30].…”
Section: Laboratory Findings In Ksmentioning
confidence: 99%